Selective reoperation after primary resection as a feasible and safe treatment strategy for recurrent pancreatic cancer. Issue 30 (July 2016) - Chang, Shih-Chun; Hsu, Chih-Po; Tsai, Chun-Yi; Liu, Yu-Yin; Liu, Keng-Hao; Hsu, Jun-Te; Yeh, Ta-Sen; Yeh, Chun-Nan; Hwang, Tsann-Long
Abstract : Abstract: Local recurrence frequently occurs in patients with pancreatic cancer after intended curative resections. However, no treatment strategies have been established for isolated local recurrence. Several series have demonstrated a survival benefit for reoperation in selected pancreatic recurrence cases. This study compares the difference in overall survival (OS) between surgery and nonsurgery groups in recurrent pancreatic cancer. All patients from 1990 to 2014 with recurrent pancreatic cancer who underwent curative resections were investigated and retrospectively reviewed. Clinicopathological features and OS were compared. A total of 332 patients were recruited in this series. The majority had histologically pancreatic adenocarcinoma (289 patients, 87.0%). Fourteen of 332 patients (4.2%) with recurrent pancreatic cancer received subsequent resection. Most of these patients underwent curative surgery (R0 resection, 13 patients, 92.9%), and only 1 patient (7.1%) had microscopic residual tumor (R1 resection). Disease-free survival (DFS), OS, and postrecurrence survival (PRS) were all significantly longer in the surgery group (DFS 10.6 vs 6.1 months, P = 0.044; OS 57.8 vs 14.0 months, P < 0.001; PRS 14.1 vs 6.0 months, P < 0.001). The median survival times were comparable in patients with recurrent pancreatic adenocarcinoma who received surgery and those who did not (DFS 10.6 vs 6.1 months, P = 0.226; OS 23.7 vs 14.0 months, P = 0.074; PRS 8.9 vs 5.8 months, P = 0.183). However, the OS and PRS were superior in the patients who did not display adenocarcinoma histologically but underwent operation for recurrence (OS 97.2 vs 16.9 months, P = 0.016; PRS 65.7 vs 6.9 months, P = 0.010). Notably, DFS levels were similar (16.0 vs 7.0 months, P = 0.265). Surgery can feasibly and safely provide survival benefits in selective recurrent pancreatic cancer. In patients who are histologically negative for adenocarcinoma, survival is prolonged when the operation is performed with R0 resection. Patients with isolated recurrent pancreatic adenocarcinoma need multidisciplinary therapy. In addition to operation, chemoradiotherapy and intraoperative radiotherapy may also be considered; their roles should be further investigated.